Neural correlates of abnormal cognitive conflict resolution in major depression: An event-related potential study - Sun, Ru-hong; Zhang, Jia-zhao; Jin, Sha-yu; Jiang, Chen-guang; Gao, Xue-zheng; Wang, Jun; Zhou, Zhen-he (Frontiers in Psychiatry, 2022)
Abnormal cognitive conflict resolution has been considered as a critical element of executive dysfunctions in patient with major depression (MD). Further clarifying whether there was a deficit at perceptual encoding stage or the early response-execution stage in conflict control function by ERP technique in MD would be helpful in understanding the neural mechanism of MD. Participants included twenty-six depressed patients and twenty-six healthy controls (HCs). All participants measured with HAMD and a Simon task. Electroencephalograms were synchronously recorded when performing the Simon task. The method of residue iteration decomposition was used to analyze the lateralized readiness potential (LRP) and P300 components, which contributed to divides ERP components into a stimulus-locked component (S-cluster), a response-locked component (R-cluster) and an intermediate component cluster (C-cluster) by using latency variability and time markers. Results showed that reactive times (RTs) for both groups were fastest in congruent trials, and slowest in incongruent trials; however, there is no difference in RTs under the three conditions between two groups. ACC for both groups were highest in neutral trials, and lowest in incongruent trials; ACC in MD group were all lower than that of HC group under three conditions. ERP data analyses showed that depressed patients had a deficit in activating the correct response, as reflected by reduced amplitudes of R-LRP, but no abnormality in LRP-S and P300-C. In conclusion, patients with MD present conflict control dysfunction (i.e., abnormal cognitive conflict resolution) at the early response-execution stage, not at perceptual encoding stage, which may be reflected by the reduced R-LRP amplitudes. The abnormal cognitive conflict resolution in activating the correct response might constitute an interesting treatment target.